Pathological Changes in Microvascular Morphology, Density, Size and Responses Following Comorbid Cerebral Injury - Amtul, Zareen; Yang, Jun; Lee, Ting-Yim; Cechetto, David F. (Frontiers in Aging Neuroscience, 2019)
Aberrations in brain microcirculation and the associated increase in blood-brain-barrier (BBB) permeability in addition to neuroinflammation and Adeposition observed in Alzheimer’s disease (AD) and ischemia have gained considerable attention recently. However, the role of microvascular homeostasis as a pathogenic substrate to disturbed microperfusion as well as an overlapping etiologic mechanism between AD and ischemia has not been thoroughly explored. In this study, we employ temporal histopathology of cerebral vasculature in a rat model of -amyloid (A) toxicity and endothelin-1 induced-ischemia (ET1) to investigate the panorama of cerebral pathology and the proteomic expression on d1, d7 and d28 post-injury. The combination of AandET1 pathological states leads to an alteration in microvascular anatomy, texture, diameter, density, and proteomic expression, in addition to disturbed vessel-matrix-connections, inter-compartmental water exchange and basement membrane profile within the lesion epicenter localized in the striatum of A+ET1 brains compared to Aand ET1 rats. We conclude that the neural microvascular network, in addition to the neural tissue, is not only sensitive to structural deterioration but also serves as an underlying vascular etiology between ischemia and AD pathologies. Such investigation can provide prospects to appreciate the interrelationships between structure and responses of cerebral microvasculature and to provide a venue for vascular remodeling as a new treatment strategy.